2022
DOI: 10.1186/s12967-022-03336-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of laboratory-based and non-laboratory-based WHO cardiovascular disease risk charts: a population-based study

Abstract: Background Determining the risk of Cardiovascular Disease (CVD) is a necessity for timely preventive interventions in high-risk groups. However, laboratory testing may be impractical in countries with limited resources. This study aimed at comparison and assessment of the agreement between laboratory-based and non-laboratory-based WHO risk charts models. Methods This study was performed using the baseline data of 8138 participants in the pars cohor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…Additionally, for a threshold of 10-year CHD risk > 20%, the corresponding agreement ranged from 94.9 to 96.5% and 96.6–97.9% for men and women, respectively [ 27 ]. Rezaei and et al by using WHO risk model showed that the non-laboratory-based risk prediction model classifies individuals almost identically to the laboratory-based model [ 18 ]. The results of a study showed that BMI is a good proxy blood sugar, and serum cholesterol [ 9 , 10 ], which could replace these variables in settings where cost may be more prohibitive for using the laboratory-based model.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, for a threshold of 10-year CHD risk > 20%, the corresponding agreement ranged from 94.9 to 96.5% and 96.6–97.9% for men and women, respectively [ 27 ]. Rezaei and et al by using WHO risk model showed that the non-laboratory-based risk prediction model classifies individuals almost identically to the laboratory-based model [ 18 ]. The results of a study showed that BMI is a good proxy blood sugar, and serum cholesterol [ 9 , 10 ], which could replace these variables in settings where cost may be more prohibitive for using the laboratory-based model.…”
Section: Discussionmentioning
confidence: 99%
“…Routine CVD risk screening and education regarding modifiable risk factors supported occupational professional standards for EBP implementation during opportune encounters with this high-risk population. limited (Jones et al, 2015;Rezaei et al, 2021Rezaei et al, , 2022. Nonlaboratory risk models have been validated and provided reliable results with superior sensitivity and specificity when compared to other CVD risk algorithms (Gaziano et al, 2008;Kariuki et al, 2017;Rezaei et al, 2022).…”
Section: Applications To Professional Practicementioning
confidence: 97%
“…BP was measured in the sitting position using a mercury sphygmomanometer after five minutes of rest. For each person, BP was measured twice on each arm and the average value was recorded (13,14). According to the JNC8 criteria, hypertension was defined as SBP ≥ 140 mmHg, or diastolic blood pressure (DBP) ≥ 90 mmHg (19), or taking medications.…”
Section: Definition Of Variablesmentioning
confidence: 99%
“…International clinical guidelines for accurate identification and subsequent evidence-based treatment of people at high risk for CVD have recommended the application of CVD risk assessment tools in routine clinical practice (11). In Iran, some studies have used different CVD risk prediction models such as FRS and WHO charts (12)(13)(14). In 2017, a risk chart for CVD in Eastern Mediterranean Region was presented by Sarrafzadegan et al (15).…”
Section: Introductionmentioning
confidence: 99%